ANSWER
![6](https://img.qammunity.org/2023/formulas/mathematics/college/pc6x99c60qwucidjk4ealyo6hmi9j7d7en.png)
Step-by-step explanation
We want to find the first term of the sequence.
The general equation for the nth term a geometric sequence is written as:
![a_n=ar^(n-1)](https://img.qammunity.org/2023/formulas/mathematics/college/ap7tka3z5szz7gan7yzwlm8df4q559etdo.png)
where a = first term; r = common ratio
Let us use this to write the equations for the third term and the fifth term.
For the third term, n = 3:
![\begin{gathered} a_3=ar^2 \\ \Rightarrow54=ar^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/w6l6i8kq2xz7oica1rh3rz8qrbppu5l2hh.png)
For the fifth term, n = 5:
![\begin{gathered} a_5=ar^4 \\ \Rightarrow486=ar^4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/r7qme48d17a0k8gp8ahhw3zcf1taxwnhdn.png)
Let us make a the subject of both formula:
![\begin{gathered} 54=ar^2_{} \\ \Rightarrow a=(54)/(r^2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/eaq52qdyp51xqwpmld3oyq1o0evau9fgcz.png)
and:
![\begin{gathered} 486_{}=ar^4 \\ a=(486)/(r^4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8vg70m3q31z1evicl1xvsjnqqrgb7tzujj.png)
Now, equate both equations above and solve for r:
![\begin{gathered} (54)/(r^2)=(486)/(r^4) \\ \Rightarrow(r^4)/(r^2)=(486)/(54) \\ \Rightarrow r^(4-2)=9 \\ \Rightarrow r^2=9 \\ \Rightarrow r=\sqrt[]{9} \\ r=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/osr8odjk01w67aeil6z7l4fios8ae3cedp.png)
Now that we have the common ratio, we can solve for a using the first equation for a:
![\begin{gathered} a=(54)/(r^2) \\ \Rightarrow a=(54)/(3^2)=(54)/(9) \\ a=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mhy2tchg6wbbep4vg6u6b0m50pb6bqkxg4.png)
That is the first term.